Downsizing big science: strategic choices. - Lambright, W. Henry (Public Administration Review)
In the current era of cutback management and downsizing in government, agencies must cope with sharply diminished resources. Strategies suitable for cutback eras include resistance, mitigation, and a mix of the two. Resistance demands that an agency confront adversaries, stand firm, mobilize the constituency, and fight. In using a mitigation strategy, leaders anticipate cutbacks, plan for them, and try to control damage through adaptation. The goal of these strategies is not the usual one of survival and growth but one of survival and stability. NASA's Big Science satellite program, until recently called Mission to Planet Earth, is examined to illustrate these strategies, and the Space Station and the Department of Energy's Superconducting Supercollider are discussed for comparison purposes.